Fra Ferrara e Napoli: percorsi bucolici - Cristina Montagnani (Annali Online dell'Università di Ferrara. Sezione Lettere)
The essay takes into consideration Matteo Maria Boiardo’s eclogues in the vernacular and puts forward the hypothesis that it is possible to identify evidence of the influence left by the Estense text on subsequent Neapolitan bucolic production.